2020
DOI: 10.1186/s12862-020-01671-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination systems in reptiles are related to ambient temperature but not to the level of climatic fluctuation

Abstract: Background: Vertebrates exhibit diverse sex determination systems and reptiles stand out by having highly variable sex determinations that include temperature-dependent and genotypic sex determination (TSD and GSD, respectively). Theory predicts that populations living in either highly variable or cold climatic conditions should evolve genotypic sex determination to buffer the populations from extreme sex ratios, yet these fundamental predictions have not been tested across a wide range of taxa. Results: Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 70 publications
0
25
1
Order By: Relevance
“…Variation in sex determination systems has been linked to a multitude of extrinsic and intrinsic factors, for example ecological patterns such as variation in ambient temperature (Cornejo‐Páramo et al. 2020; Pen et al. 2010), life‐history parameters such as longevity (Janzen & Paukstis, 1991a,b; Sabath et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in sex determination systems has been linked to a multitude of extrinsic and intrinsic factors, for example ecological patterns such as variation in ambient temperature (Cornejo‐Páramo et al. 2020; Pen et al. 2010), life‐history parameters such as longevity (Janzen & Paukstis, 1991a,b; Sabath et al.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in sex determination systems has been linked to a multitude of extrinsic and intrinsic factors, for example ecological patterns such as variation in ambient temperature (Cornejo-Páramo et al 2020;Pen et al 2010), life-history parameters such as longevity (Janzen & Paukstis, 1991a,b;Sabath et al 2016), reproductive mode (Organ et al, 2009) and demographic composition of the populations expressed as adult sex ratio (Pipoly et al 2015). A link between sex determination and sexual size dimorphism is also suggested, either by direct physiological causation or indirectly, acting through the above-mentioned mediators (Adkins-Regan & Reeve, 2014;Ewert et al 1994;Ewert & Nelson, 1991;Janzen & Paukstis, 1991a,b;Kraak, 1994;Schwanz et al 2016;Viets et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, B. vittatus does not appear to show temperature-dependent sex reversal within the 26-32°C temperature range. We selected these incubation temperatures because they are common male-producing or female-producing temperatures in non-avian reptiles and because they represent average temperatures during the reproductive season of B. vittatus [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, [11] it has been suggested that the evolution of SDS systems in reptiles is related to temperature environment rather than to environmental temperature fluctuations. In particular, the authors reported that TSD species were more frequent in warmer climates cand GSD more frequent in cooler ones.…”
Section: Ectothermic-tsd Species Breed At Temperature That Maximize E...mentioning
confidence: 99%